Influência dos marcadores de hipoperfusão tecidual na força muscular periférica e capacidade funcional em pacientes pós-operatório de cirurgia cardíaca - BORGES, Mayara Gabrielle Barbosa (2017)
The mismatching between supply and oxygen consumption due to intra and postoperative factors leads to several cardiac surgery postoperative complications, which may reduce peripheral muscle strength (PMS) and impair functional capacity. This research proposes to evaluate the repercussion of markers of tissue perfusion in PMS and functional capacity of patients submitted to cardiac surgery. It is a prospective cohort study, performed at Hospital Universitário da Universidade Federal do Maranhão, in São Luís – MA, with 72 participants who underwent cardiac surgery and were admitted to the Cardiac Intensive Care Unit (Cardiac ICU) between January and December, 2016. Peripheral muscle strength, by a hydraulic handgrip dynamometer and functional capacity, through the Functional Independence Measure (FIM), were assessed preoperatively and on the sixth postoperative day. Arterial lactate, central venous oxygen saturation (ScvO2) and arteriovenous difference of carbon dioxide (ΔpCO2) were evaluated by arterial and venous blood gases, collected at four periods: anesthesia pre-induction (T0), admission to the ICU (T1), six (T2) and 12 hours (T3) after admission to the ICU. Regarding peripheral muscle strength, there was a reduction in both dominant (p= 0,03) and non-dominant hands (p= 0,004), when comparing pre and postoperative periods, as well as functional capacity (p < 0,0001). No correlation was found between the markers of tissue perfusion and functional outcomes assessed. Therefore, in this sample, cardiac surgery led to repercussions on functional capacity and PMS when assessed at the hospital. However, However, the stratification of the groups regarding the type of surgery in relation to the FMP showed a weak negative correlation of the ΔpCO2 of the T1 of the dominant hand (p = 0,04; r = -0,36) and of the non-dominant hand (p = 0,04; r = -0.36) in patients undergoing coronary artery bypass grafting. Therefore, in this sample, cardiac surgery caused damages in functional capacity and MPF when measured still in a hospital environment. In addition, patients undergoing coronary artery bypass g